2011
DOI: 10.1007/s00438-010-0598-4
|View full text |Cite
|
Sign up to set email alerts
|

The first insight into the Taxus genome via fosmid library construction and end sequencing

Abstract: Taxus mairei is a critically endangered and commercially important cultured medicinal gymnosperm in China and forms an important medicinal resource, but the research of its genome is absent. In this study, we constructed a T. mairei fosmid library and analyzed the fosmid end sequences to provide a preliminary assessment of the genome. The library consists of one million clones with an average insert size of about 39 kb, amounting to 3.9 genome equivalents. Fosmid stability assays indicate that T. mairei DNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
(42 reference statements)
2
27
0
Order By: Relevance
“…Almost twice as many genes (62,654 vs. 36,493) were assembled in the present study as previously reported (Hao et al, 2011). This may be due to the existence of cold activated genes, as overall, 29,783 transcripts up-regulated under cold stressed condition by a factor of 4 (|log 2 FC|> 2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Almost twice as many genes (62,654 vs. 36,493) were assembled in the present study as previously reported (Hao et al, 2011). This may be due to the existence of cold activated genes, as overall, 29,783 transcripts up-regulated under cold stressed condition by a factor of 4 (|log 2 FC|> 2).…”
Section: Discussionsupporting
confidence: 79%
“…The transcriptome of the genus Taxus has been previously reported for gene expression profiles in leaf, stem, and root tissues using Illumina sequencing (Hao et al, 2011) and in needles using 454 pyrosequencing (Wu et al, 2011). However, information on the large-scale regulation of gene expression profiles in response to cold stress is still lacking for this temperature-sensitive genus.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of contigs, as well as the mean length, the N 50 length, and GC% were recorded. The contigs were further assembled into sequences that could not be extended at either end; these are called unigenes (having 94% identity, 30 bp overlap) [34,35]. Such unigenes were subjected to annotation analysis against public protein and nucleotide databases.…”
Section: Methodsmentioning
confidence: 99%
“…As opposed to the high technical skills and costs required to develop large-insert deep-coverage BAC libraries, Fosmid library construction remains quite trivial [33]. The narrower insert range, stable maintenance, and easy production have made Fosmids suitable for a wide range of applications [30, 34]. For instance, Fosmid libraries per se are useful for whole-genome physical mapping [3537] and refining the BAC/PAC-based physical maps by effective gap filling [26, 30].…”
Section: Fosmids As a Tool For Physical Mappingmentioning
confidence: 99%
“…For instance, Fosmid libraries per se are useful for whole-genome physical mapping [3537] and refining the BAC/PAC-based physical maps by effective gap filling [26, 30]. Furthermore, paired Fosmid end sequences, due to the narrower insert size range of Fosmid clones, are useful for sequence scaffolding in large-scale sequencing projects and studies related to structural variation and organization of the genomes [34, 3841]. …”
Section: Fosmids As a Tool For Physical Mappingmentioning
confidence: 99%